The risk of infective endocarditis following interventional pulmonary valve implantation: A meta-analysis. Issue 3 (September 2019) - Lehner, Anja; Haas, Nikolaus A.; Dietl, Markus; Jakob, Andre; Schulze-Neick, Ingram; Dalla Pozza, Robert; Rodriguez, Silvia Fernandez; Fischer, Marcus
Highlights: Currently 2 types of percutaneous pulmonary valves are available for implantation. Melody ® valve (Medtronic, Dublin, Ireland) and Sapien™ valves (Edwards Lifesciences, Irvine, CA, USA). There is still no consensus in the guidelines which type of valve is better suited. Using Melody ® valves carries a substantially higher risk of developing infective endocarditis. Abstract: Background: Interventional percutaneous pulmonary valve implantation (PPVI) was first reported in 2000. Today, two different valves are certified for this procedure [i.e. Medtronic Melody ® valve (Medtronic, Dublin, Ireland) and Edwards Sapien™ valve (Edwards Lifesciences, Irvine, CA, USA)]. For a decade, studies have reported an increasing risk of infective endocarditis (IE) after PPVI; as patients for PPVI are usually younger, even a low annual incidence of IE is important. However, the overall incidence and potential differences between the valves remain unclear. Methods: A systematic literature search was performed in the databases Medline, Cochrane Library, and Embase including the clinical trials register. The aim was to summarize and compare the cumulative incidence of IE after PPVI. Using a sensitivity analysis we set the incidence rates of the two valve types in ratio with a normal population. Results: A total of 967 publications were identified searching for "pulmonary valve implantation, " "PPVI, " and 47 publications were used for final analysis. A total 3616 patients with Melody ® valves and 501 with Sapien™ valves were included. IE after PPVI occurred in 214 patients with Melody ® valves and in 5 patients only with Sapien™ valves. The pooled incidence for Melody ® and Sapien™ valves was 4.9% (95% CI: 3.6–6.2) and 1.3% (95% CI: 0.3–2.3), respectively. Chi-square test was significant. The sensitivity analysis showed that the incidence rate ratio was 252.1 (95% CI: 187.6–338.6) for Melody ® valves and for Sapien™ valves 2.7 (95% CI: 0.8–9.2). Conclusions: At present, there is an important difference for the risk of IE after PPVI. To reduce the risk of post PPVI endocarditis, a careful valve selection in favor of the Sapien™ valves seems to be beneficial.